Pengaruh Bahasa Gaul Terhadap Eksistensi Bahasa Indonesia Pada Anak Remaja Desa Ujung Lamuru Kecamatan Lappariaja Kabupaten Bone - Iskandar Iskandar; Muhammad Dahlan; Andi Sosila Kamaruddin (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this service is to explain the existence of the slang language spoken which is influenced by social media, almost all students use it. This research aims to analyze the influence of slang on the existence of the Indonesian language, with a focus on the case study of students at Muhammadiyah University of Makassar. The use of slang among students has become an increasingly widespread phenomenon, raising questions regarding its impact on the use and maintenance of Indonesian as the country's official language. This research method involves qualitative research analysis using a structured descriptive method on a number of students from the Indonesian Language and Literature Education department at Muhammadiyah University of Makassar. This research was designed to identify the level of understanding and use of slang and describe the complexity of the dynamics between slang use and maintenance of Indonesian. This research contributes to our understanding of how the slang phenomenon influences the existence of Indonesian in society, especially in Ujung Lamuru village. The implications of this research can provide a basis for designing educational strategies and language awareness that are more effective in maintaining the existence of the Indonesian language in this modern era. Slang can be said to be a certain code that only a group of people know the meaning and purpose of.